O gênero fábula nas aulas de língua portuguesa no desenvolvimento das competências leitoras do 7º ano da escola Tenente Turiano Silva – Titular - SILVA, Sueli dos Santos (2019)
The present work aims to present a didactic sequence that has as object of study the fable textual genre for its dissemination in the society in which we live to develop the reading competence in 7th grade students of the Municipal School of Primary Education Tenente Turiano Silva - Titular. The general objective of this methodological proposal is to stimulate the habit of reading, allowing the development of interpretive skills, understanding the importance of reading for their formation, and the specific objectives are: to identify the fable genre and its peculiarities; develop reading competence for 7th grade students; develop oral communication skills, improving the student's speech, reading and writing skills. In order to guide this work, Bakhtin's dialogical conception of language (2011), Marcuschi's (2008) studies on textual genre and textual type were taken as theoretical reference; and the proposal of Dolz and Schnewly (2004) to apply didactic sequence for mother tongue teaching. The methodology used was the bibliographical research and presentation of a proposal to work the textual genre fable in the 7th year of elementary school.